ANALISIS KESALAHAN PESERTA DIDIK FASE E DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TEORI KESALAHAN NEWMAN (STUDI KASUS SMA NEGERI 8 PADANG) - Lutfiah, Ulfa (Departemen Matematika, 2023)
The aim of this research is to elucidate and analyze the errors made by SMA Negeri 8 Padang Phase E students when attempting to solve word problems on a system of three-variable linear equations based on Newman's error theory. The errors studied were based on the types of error indicators of Newman's errors which included inaccuracies in reading the questions, inaccuracies in understanding the questions, inaccuracies in the transformation of the questions, inaccuracies in processing skills and errors in writing the final answer. The results showed that the research subjects tended to make (a) The percentage of errors in process skills is 35%.; (b) The percentage of errors in the transformation is 30%.; (c) The percentage of errors in comprehend the problem is 17%.; (d)The percentage of errors in writing the final answer is 11%; (e) The percentage of errors in reading the questions is 7%.Keywords: Student error analysis, newman's error theory, math word problems.